Diet-supported aerobic exercise reduces blood endothelin-1 and nitric oxide levels in individuals with impaired glucose tolerance - YEGEN, BERRAK; YAVUZ, DİLEK; KURTEL, HIZIR; KASIMAY ÇAKIR, ÖZGÜR (ELSEVIER SCIENCE INC, 2010)
BACKGROUND: Impaired glucose tolerance (IGT) forms an intermediate stage in the natural history of diabetes mellitus. Insulin-resistant states might be associated with dysfunction of the vascular endothelium. OBJECTIVES: To determine the effects of chronic exercise and a low-calorie diet on plasma nitric oxide (NO) and endothelin-1 (ET-1) levels in patients with JOT and to elucidate the relationship between the oxidant stress markers and NO/ET-1 levels of blood before and after exercise. METHODS: Patients with IGT (n = 14) participated in a regular exercise program and exercised for 40 minutes each day, 3 days a week for 12 weeks. Physiological, anthropometric, and biochemical measurements were performed before, during the 6th week, and at the end of the program. RESULTS: There was a significant reduction in body mass index, body fat content, systolic and diastolic blood pressures, as well as NO and ET-1 concentrations after 12 weeks of exercise and diet program. Exercise training significantly elevated subjects' maximum oxygen consumption, whereas the resting metabolic rates of the patients did not change. The formation of thiobarbituric acid reactive substances were significantly reduced, whereas sulfhydryl groups were significantly increased on the 6th week (P < .05) and at the end of program (P < .01). CONCLUSION: Our results demonstrate that exercise, along with low-calorie diet, induced reductions in the plasma of both ET-1 and NO. Beneficial effects were observed on anthropometric measurements and plasma oxidant stress markers, indicating weight loss associated with exercise training and calorie restriction may effectively improve endothelial dysfunction in patients with IGT. (C) 2010 National Lipid Association. All rights reserved.
Keywords: Blood pressure; Endothelin-1; Exercise; Impaired glucose tolerance; Nitric oxide; Plasma sulfhydryl (RSH) groups; Plasma TBARS; TYPE-2 DIABETES-MELLITUS; PLASMA ENDOTHELIN-1; INSULIN-RESISTANCE; DYSFUNCTION; METABOLISM; HUMANS; SYNTHASE; TISSUE